A Study of Evaluation Influence in Two Child Protection Programs. (December 2022) - Herbert, James Leslie
Evaluation influence is a reconceptualization of evaluation use that reflects the broad and diffuse impacts an evaluation can have on social programs and policies. This way of thinking about impact provides an opportunity to investigate how and why evaluations influence social programs and policy. Twenty participants (practitioners and managers) from two child protection programs evaluated in the previous 24 months were interviewed about the influence of these evaluations, which was complemented with the collection of internal documents about changes to the programs. A qualitative case study analysis of evaluation influence was conducted using the interviews and documents to investigate the influence of two evaluations at different stages in the dissemination process. The participants identified that the evaluations appeared to have significant high-level policy level influence; however, limited examples of influence on practices in the programs were identified. There was some suggestion that the evaluations had increased practitioner interest in working with and participating in program evaluations. The findings suggest the importance of developmental evaluation approaches and practitioner engagement in evaluation to improve the influence and adoption of new knowledge from the evaluation of social programs.